Covering peak demand by using cloud services – an economic analysis. Issue 2 (2nd April 2016) - Henneberger, Matthias
Abstract: By using cloud services, companies can access computing capacity on demand, paying only for the capacity that is actually used. This makes cloud services especially interesting for covering peak demand. In this paper, we evaluate under which conditions such a strategy is economically reasonable. We develop a simplified stochastic optimisation model that is suited to support cloud computing decisions. Analysing the model reveals that – under certain assumptions – it is always reasonable to use cloud services to cover peak demand, even if the price is high or if service levels are low. Furthermore, it turns out that higher variance of demand for capacity should not automatically result into a more extensive use of cloud services. These findings as well as our modelling approach can support companies to increase the value of their information technology (IT) infrastructure by leveraging cloud services.